2019
DOI: 10.1002/wsb.948
|View full text |Cite
|
Sign up to set email alerts
|

Meeting harvest expectations is key for duck hunter satisfaction

Abstract: Current literature suggests that seeing and bagging game, among other experiences, play a major role in overall satisfaction for hunters. In addition, research highlights relationships that harvest expectations may have with harvest success and in explaining satisfaction. We add to the multiple satisfactions concept that, despite other derived benefits, harvest success may be fundamental to sustain participation and duck (Anatidae) hunters themselves are agents of their own success. We used data from mail surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…In Canada, hunters with dogs and decoys fired more shots and bagged more ducks than hunters not using these tools (Boyd 1971), and spinning-wing decoys have been effective in attracting ducks within shooting range (Ackerman et al 2006). In our study, parties with a higher investment index also were slightly less satisfied than parties with a lower index, suggesting that hunters who invested more in associated equipment may tend to be more achievement-oriented (Decker et al 1984, Enck et al 1993) and have higher harvest expectations (Brunke and Hunt 2008, Bradshaw et al 2019, Schroeder et al 2019. Hunting parties used the full spectrum of equipment combinations, and from no equipment to 18 dozen standard decoys, 2 spinning-wing decoys, and dogs.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In Canada, hunters with dogs and decoys fired more shots and bagged more ducks than hunters not using these tools (Boyd 1971), and spinning-wing decoys have been effective in attracting ducks within shooting range (Ackerman et al 2006). In our study, parties with a higher investment index also were slightly less satisfied than parties with a lower index, suggesting that hunters who invested more in associated equipment may tend to be more achievement-oriented (Decker et al 1984, Enck et al 1993) and have higher harvest expectations (Brunke and Hunt 2008, Bradshaw et al 2019, Schroeder et al 2019. Hunting parties used the full spectrum of equipment combinations, and from no equipment to 18 dozen standard decoys, 2 spinning-wing decoys, and dogs.…”
Section: Discussionmentioning
confidence: 60%
“…Numerous researchers reported that success in bagging game is an important component in waterfowl hunter satisfaction (Brunke and Hunt 2008, Ebeling‐Schuld and Carimont 2017, Bradshaw et al 2019, Schroeder et al 2019, Gruntorad et al 2020). Because weather influences duck movements (Jorde et al 1984), and may directly affect hunters' expectations and enjoyment being in the field, we predicted temperature and precipitation would influence a hunting party's satisfaction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most often, measures of the social correlates of satisfaction have been bound by the temporal extent of hunting events such as contact within and across hunting parties (Hautaluoma and Brown 1978), hunter density (Hammitt et al 1990, Heberlein 2002, and companionship while hunting (Hazel et al 1990, Hayslette et al 2001. The lack of contact with or interference from other hunters (Gruntorad et al 2020), even while the consideration of other determinants of satisfaction such as hunter knowledge, experience and skill (Hammitt et al 1990, Frey et al 2003, access to private land (Gruntorad et al 2020), or training a dog (Bradshaw et al 2019) has been far less constrained. Missing is a recognition of the broader sociocultural environment of hunters (Larson et al 2014).…”
mentioning
confidence: 99%
“…Recruitment, retention, and reactivation efforts (R3) of hunters often focuses on improving hunting experiences (Humburg et al 2018, Schummer et al 2020). Social science researchers suggest viewing and having the potential to harvest game enhances hunt quality and satisfaction (Fulton et al 2017, Bradshaw et al 2019, Schroeder et al 2019, Schummer et al 2020). Thus, identifying factors associated with seeing, shooting at, and harvesting more game may yield important insights to promote hunter satisfaction and engagement (Ringelman and Rubec 1997).…”
Section: Hypothesis Variable Description Predicted Relationshipmentioning
confidence: 99%